In vitro antagonism test of endophytic isolates from the ciplukan plant (Physalis angulata L.) against Ralstonia solanacearums - Ika Afifah Nugraheni; Inneke Ashri Mawaddah (Universitas Insan Cendekia Mandiri, 2023)
Ralstonia solanacearum was a pathogenic bacteria that causes wilt disease which can cause up to one hundred percent damage to horticultural plants. Therefore, a control effort was needed to overcome this problem. The use of pesticides was an alternative that can be used to suppress the growth of the pathogen R. solanacearum. However, its continuous use poses a high risk to the environment so friendly and safe control efforts are needed. One way was by utilizing endophytic bacteria. This study aims to test the ability of endophytic bacterial isolates from ciplukan plant (Physalis angulata L.) to suppress the growth of the pathogenic bacteria R. solanacearum in vitro. The method in this research includes rejuvenating endophytic bacterial isolates BA2(3), BA3(1), DA1(4) and BU3(5) from ciplukan plants (Physalis angulata L.) obtained from research conducted by Setianah (2020), observations macroscopic and microscopic endophyte isolates, hypersensitivity test of endophytic bacteria on tobacco plants (Nicotiana tabacum L.), then continued with an in vitro antagonist test using the Kirby Baurer technique. Research data shows that of the four candidates, two isolates of endophytic bacteria, namely BA2(3) and BU3(5), showed a negative hypersensitivity reaction which was characterized by the absence of necrosis symptoms in the hypersensitivity test, so these isolates could be tested for antagonists. The results of the antagonist test showed that isolates BA2(3) and BU3(5) had the potential to inhibit the growth of R. solanacearum which had an inhibitory diameter of 3.03 mm and 1.60 mm in the first 24 hours of incubation. It is hoped that the ability of endophyte isolates BA2(3) and BU3(5) to inhibit the growth of the pathogen R. solanacearum can be used as a biological agent to reduce the use of pesticides in treating plant diseases.